Proceedings of the 3rd Pan American Materials Congress - Meyers, Marc André; Benavides, Hector Alfredo Calderon; Brühl, Sonia P.; Colorado, Henry A.; Dalgaard, Elvi.; Elias, Carlos Nelson; Figueiredo, Roberto B.; Garcia-Rincon, Omar.; Kawasaki, Megumi; Langdon, Terence G.; Mangalaraja, R.V.; Marroquin, Mery Cecilia Gomez; et al. (Cham : Springer International Publishing : Imprint: Springer, 2017)
This collection covers a variety of materials science topics and has contributions from leading scientists and engineers representing 8 countries and 9 international materials, metals, and minerals societies. Papers are organized into the following sections: Advanced Biomaterials Advanced Manufacturing Materials for Green Energy Materials for Infrastructure Materials for the Oil and Gas Industry Materials for Transportation and Lightweighting Minerals Extraction and Processing Nanocrystalline and Ultra-fine Grain Materials and Bulk Metallic Glasses Steels.
Part 1: Pan American Materials Congress: Advanced Biomaterials -- Analysis of Biomimetic Surgical Clip Using Finite Element Modeling for Geometry Improvement and Biomaterials Selection -- Chemical composition effect of sol-gel derived bioactive glass over bioactivity behavior -- Effects of Dialium guineense based zinc nanoparticle material on the inhibition of microbes inducing microbiologically influenced corrosion -- Injectability evaluation of bone-graft substitutes based on carrageenan and hydroxyapatite nanorods -- Synthesis and characterization of Ni0.5Zn0.5Fe2O4@mSiO2 core shell nanocarrier for drug delivery applications -- Part 2: Pan American Materials Congress: Advanced Manufacturing -- Carbon Based Coatings Deposited On Nitrided Stainless Steel: Study Of Thermal Degradation -- Comparative Mechanical Analysis Between Epoxy Composite Reinforced With Random Short Cuarua Fibers And Aligned Long Curaua Fibers -- Effect of Tool Rotation on Tool Wear Phenomenon in Rotary Tool micro-USM -- Numerical Modeling of High-Velocity Impact Welding -- Selective Laser Sintering of Polyamide/Hydroxyapatite Scaffolds -- Part 3: Pan American Materials Congress: Materials for Green Energy -- A comparison between recycled spent zeolite and calcite limestone for manganese removal -- Effect of Mo6+ Substitution on Microstructure and Lithium Ionic Conductivity of Garnet-Type Li7La3Zr2O12 Solid Electrolytes by Field Assisted Sintering Technology -- Electromagnetic Levitation Refining Of Silicon-iron Alloys for Generation of Solar Grade Silicon -- Green Extract of Mate Tea as Corrosion Inhibitor of Copper and Aluminum -- Platinum Salts Synthesis as Precursors to Get Heterogeneous Catalysts for Biofuels Production -- Technical and Environmental Assessment of an Alternative Binder for Low Traffic Roads with LCA Methodology -- Part 4: Pan American Materials Congress: Materials for Infrastructure -- Anticorrosion and Adsorption Mechanism of Rhizophora mangle L Leaf-extract on Steel-reinforcement in 3.5% NaCl-immersed Concrete -- Cassia fistula leaf-extract Effect on Corrosion-inhibition of Stainless-steel in 0.5 M HCl -- Effect of C5H11NO2S on Reinforcing-steel Corrosion in Concrete Immersed in Industrial/Microbial Simulating-environment -- FIBER REINFORCED CONCRETE MANUFACTURED WITH ELECTRIC ARC FURNACE SLAG -- Jigs, hydro-cyclones and sensor-based sorting to value recycled aggregates -- Performance of hydraulic mixes manufactured with electric arc furnace slag aggregates -- POROUS ASPHALT MIXTURES WITH 100% SIDERURGIC AGGREGATES -- Part 5: Pan American Materials Congress: Materials for Oil and Gas Industry -- Blends of PVDF with its processing waste: Study of the mechanical properties of the blends thermally aged -- DYNAMIC TRANSFORMATION AND RETRANSFORMATION DURING THE SIMULATED PLATE ROLLING OF AN X70 PIPELINE STEEL -- Effect of Heat Input on the microstructure and toughness of welded API pipelines -- EVALUATION OF NON-DESTRUCTIVE TECHNIQUES (THERMOGRAPHY, ULTRASOUND AND EDDY CURRENT) FOR DETECTION OF FAILURES IN METALLIC SUBSTRATES WITH COMPOSITE ANTICORROSIVE COATINGS -- Structural Integrity of Pipelines -- Part 6: Pan American Materials Congress: Materials for Transportation and Lightweighting -- ADVANTAGES OF HOT COMPRESSION IN THE MANUFACTURE OF AlB4C COMPOSITES -- An Improved Silicon Carbide Monofilament for the Reinforcement of Metal Matrix Composites -- Analysis of coir fiber porosity -- BALLISTIC PERFORMANCE IN MULTILAYER ARMOR WITH EPOXY COMPOSITE REINFORCED WITH MALVA FIBERS -- Curaua non-woven fabric composite for ceramic multilayered armors: A lightweight, natural, and low cost alternative for KevlarTM -- Effect of Forging on Microstructure, Texture and Compression Behaviour of Extruded AZ31B -- EFFECTS OF HYPOEUTECTIC Sc ADDITIONS TO Al-4.5 wt% Cu UNDER DIFFERENT COOLING RATES -- IZOD IMPACT TESTS IN POLYESTER MATRIX COMPOSITES REINFORCED WITH FIQUE FABRIC -- IZOD IMPACT TESTS IN POLYESTER MATRIX COMPOSITES REINFORCED WITH JUTE FABRIC -- Microstructure and Hardness of Subzero Quenched and Heat Treated Ti-6Al-4V Alloy -- Nano-Additive Reinforcement of Thermoplastic Microballoon Epoxy Syntactic Foams -- Nanocomposites Mechanical and Tribological Properties using Graphene Coated Ceramic Nanoparticles for Light Weight Applications -- Synthesis of Energetic Composites in Ti-Al-B-C System by Adiabatic Explosive Compaction -- Tensile and impact properties of two fiber configurations for curaua reinforced composites -- Thermo\\8722;Mechanical behavior of nanostructure polyacrylic polymer based on Al2 O3 and bentonite nanoparticles -- Thermo\\8722;mechanical properties of waterborne acrylate hybrid nanocomposites -- Thermo-mechanical properties of copolymer/clay nanocomposites: A comparative study of production method by in-situ and solution mixture -- Part 7: Pan American Materials Congress: Minerals Extraction and Processing -- Biotechnological recycling of precious metals sourced from post-consumer products -- Biotechnologies for water recycling in the mineral industry -- Dissolution thermodynamics of smithsonite in alkaline iminodiacetate aqueous solution -- Effect of ethylenediamine on smithsonite flotation -- Extraction of Gold from sands and Slimes Tailings Dump from Mazowe Mine, Zimbabwe -- Gold Recovery from Waste Solutions of PCB Gold Plating Process using Hydro Cyclone Reactor for Demonstration Study -- Improving Quality of Coke Made from Chinese Xinjiang Gas Coal with High Strength Modifier -- INVESTIGATING THE DISSOLUTION CHARACTERISTICS OF STRONTIUM SULFIDE -- Kinetic study on the leaching of vanadium-bearing converter slag with dilute sulfuric acid -- Leaching of Spent Ni-Mo Hydrodesulphurization (HDS) Catalyst in Oxalic Acid Solutions -- Novel Adsorbent from Iron Ore Concentration Tailings for Toxic Cationic Dye Removal from Water -- Preliminary analysis of the application of sensor based sorting on a limestone mine in the region Caçapava do Sul, Brazil -- Preparation of high grade Industrial Copper Compound from a Nigerian Malachite mineral by Hydrometallurgical process -- PROCESS OF IMPROVING THE FLOTATION USING ULTRASONIC BOMBARDMENT -- Production of strontianite from celestite ore in carbonate media -- Reduction Kinetics and Characterization Study of Synthetic Magnetite Micro Fines -- Study on Leaching Valuable Elements from Bayan Obo Tailings -- Study on thermal decomposition and oxidation characteristics of iron ores -- The direct leaching of micro-disseminated gold concentrate by bromide process and the characterization of leaching products -- Working Experience with the new WOX Plant to treat zinc waelzoxide at ZGH Boleslaw SA, Poland -- Part 8: Pan American Materials Congress: Nanocrystalline and Ultra-fine Grain Materials and Bulk Metallic Glasses -- Continuous dynamic recovery in pure aluminum deformed to high strain by accumulative press bonding -- Effects of Natural Aging and Post-processed Heat Treatment on the Microstructure and Mechanical Properties of Friction Stir Processed Al-7B04 -- Evaluation of the hardening and softening effects in Zn-21Al-2Cu with as cast and homogenized microstructure processed by equal channel angular pressing -- Part 9: Pan American Materials Congress: Steels -- Effect of titanium sulfide precipitates on grain size in low carbon steel -- Evolution of Austenite Dislocation Density during Hot Deformation using a Physical Dynamic Recrystallization Model -- Influence of a Rapid Heating on the Microstructure and Properties of Press-Hardening Steel Sheets -- Jansto:New Generation Niobium Bearing Structural Steels for Future Infrastructure Demands -- Kinetic study of the austenite decomposition during continuous cooling in a welding steel -- Microstructural Evolution in Microalloyed Steels during Thermomechanical Rod Rolling -- MODELING OF METAL-SLAG MASS AND MOMENTUM EXCHANGES IN GAS-STIRRED LADLES -- Study on adjustment and optimization of LF refining slag of spring steel 55SiCrA -- Tempering Response of Bainitic and Martensitic Microstructures -- The research on the relationship between gas movement behaviors and circulating flow of the molten steel in RH.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering